The value of admissions characteristics for predicting the practice location of University of Saskatchewan College of Medicine graduates - Ironside, Avery; Thoma, Brent; Trinder, Krista; Bueckert, Sherrill; Lee, Tara; Domes, Trustin (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Background: The physician workforce in Saskatchewan depends upon the retention of locally trained physicians. Characteristics collected at the time of medical school application may predict future practice location, but these associations have not been explored.Methods: We identified the current practice location of University of Saskatchewan College of Medicine graduates who matriculated between 2000 and 2013 and extracted data from their admission applications including gender, age, high school, previous university, and current location at the time of application. We then conducted univariate and multivariate analyses to evaluate associations between these characteristics and rural- and Saskatchewan-based practice.Results: We identified the current practice location of 1,001 (98.9%) of the graduates of the included cohorts. Attending a Saskatchewan high school (p < 0.001), a high school in a smaller population center (p < 0.01), and a Saskatchewan university (p < 0.001) were predictive of Saskatchewan-based practice. Attending a high school outside of Saskatchewan (p < 0.05), a high school in a smaller population center (p < 0.001), and living in a small population centre at the time of application (p < 0.05) were predictive of rural-based practice within or outside of Saskatchewan.Conclusion: Demographic characteristics collected at time of medical school application are associated with future Saskatchewan- and rural-based practice. These findings will guide admissions policies in Saskatchewan and may inform admission practices of other medical schools.